2022
DOI: 10.1007/s11259-022-09945-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of phytogenic plus short and medium-chain fatty acids-based additives in enterotoxigenic Escherichia coli challenged piglets

Abstract: Post Weaning Diarrhea (PWD) is the most important multifactorial gastroenteric disease of the weaning in pig livestock. Phytogenic (PHY) natural extracts are largely studied as alternatives to antibiotic treatments in combating the global concern of the antimicrobial resistance. The aim of this study was to evaluate the protective effect of innovative phytogenic premix with or without short and medium chain fatty acids (SCFA and MCFA) in O138 Escherichia coli challenged piglets. Twenty-seven weaned piglets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Similar to acetylsalicylate compounds and products (“aspirin”), anti-inflammatory properties have been reported for methyl esters of salicylic acid and glycosides thereof [ 64 ]. Both PFAs also feature further plant-based additives and their active components with additional reported beneficial properties, e.g., a complex plant powder mix, including cinnamon bark, and its active component cinnamaldehyde [ 5 , 7 , 11 , 21 , 24 , 65 ], gentian root, grape seed and skin extract [ 66 , 67 ], and angelica root. Licorice extract, included only in D-DC2, has also been reported as a feed additive with various beneficial properties, e.g., on performance, intestinal health, and the immune system [ 12 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to acetylsalicylate compounds and products (“aspirin”), anti-inflammatory properties have been reported for methyl esters of salicylic acid and glycosides thereof [ 64 ]. Both PFAs also feature further plant-based additives and their active components with additional reported beneficial properties, e.g., a complex plant powder mix, including cinnamon bark, and its active component cinnamaldehyde [ 5 , 7 , 11 , 21 , 24 , 65 ], gentian root, grape seed and skin extract [ 66 , 67 ], and angelica root. Licorice extract, included only in D-DC2, has also been reported as a feed additive with various beneficial properties, e.g., on performance, intestinal health, and the immune system [ 12 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…PFAs are subject to various in vivo and in vitro studies across species, shedding light on diverse areas of potential activity [ 5 , 6 , 7 , 11 , 12 , 21 ] such as immunological status and inflammation [ 16 , 21 , 22 , 23 , 24 , 25 ], gastrointestinal health and barrier integrity [ 16 , 22 , 23 , 24 , 25 , 26 , 27 ], protective effects against pathogens and toxins of various kinds [ 23 , 24 , 25 , 27 ], as well as overall animal growth and performance [ 15 , 21 , 24 , 26 , 27 ]. In general, suitable in vitro models are of significant importance and many available in vitro studies assess specific subprocesses of gut functionality and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple research investigations have linked F18 + E. coli to PWD and reduced growth performance [7,16,[66][67][68]76,77,79,81,83,[85][86][87][88]. These studies on nursery pigs challenged with F18 + E. coli showed an average reduction of 27% in ADG, 10% in ADFI, and 20% in feed efficiency (Figure 4A-C).…”
Section: Physiological Clinical Immunological and Growth Responses Of...mentioning
confidence: 96%
“…Moita et al [129] reported that a blend of castor oil and cashew nutshell liquid improved the microbiota composition by increasing the abundance of Lactobacillus and Pseudomonas, while reducing the abundance of Helicobacter and Campylobacter. According to Caprarulo et al [88], the use of a blend of phytobiotics was effective in reducing the effects caused by F18 + E. coli on the growth performance by increasing G:F (51%) and health of nursery pigs by inhibiting the proliferation of pathogens and increasing the abundance of beneficial bacteria. Chang et al [85] reported that a mixture of thymol, carvacrol, and bitter citrus extract improved immune responses by reducing TNF-α (23%), IL6 (21%), and intestinal integrity resulting in an increased ADG (49%) in nursery pigs challenged with F18 + E. coli.…”
Section: Phytobioticsmentioning
confidence: 99%
“…Fatty acids have been considered an alternative to antibiotics or zinc oxide [ 4 ] as they stimulate immunity by triggering local proliferation and the adaptive immune response [ 5 ], particularly against Salmonella enteritidis and enteropathogenic Escherichia coli [ 6 , 7 ]. SCFA are pivotal as a fuel for intestinal epithelial cells and as antibacterial agents, inducing cell lysis and inhibition of enzyme activity [ 8 ], as well as stimulating gastrointestinal motility [ 9 ].…”
Section: Introductionmentioning
confidence: 99%